COMPLIANCE WITH GUIDELINES FOR PATIENTS WITH BLADDER CANCER: VARIATION IN THE DELIVERY OF CARE - Chamie, Karim (2011)
BACKGROUND: Clinical practice guidelines for the management of patients with bladder cancer encompass strategies that minimize morbidity and improve survival. We sought to characterize practice patterns in patients with high-grade non-muscle-invasive bladder cancer in relation to established guidelines. METHODS: We used Surveillance, Epidemiology and End Results (SEER)-Medicare-linked data to identify subjects diagnosed with high-grade non-muscle-invasive bladder cancer in 1992–2002 who survived at least two years without undergoing definitive treatment (n=4,545). We used multilevel modeling to estimate the association and partitioned variation of patient sociodemographic, tumor, and provider characteristics with compliance measures. RESULTS: Of 4,545 subjects analyzed, only one received all the recommended measures. Approximately 42% of physicians have not performed on a single patient nested within their practice in a two-year period, at least one cystoscopy, cytology and a single instillation of immunotherapy. After 1997, only utilization of radiographic imaging (OR 1.19; 95% CI 1.03–1.37) and instillation of immunotherapy (OR 1.67; 95% CI 1.39–2.01) significantly increased. Surgeon-attributable variation for individual guideline measures (cystoscopy 25%; cytology 59%; radiographic imaging 10%; intravesical chemotherapy 45%; and intravesical immunotherapy 26%) contributes to this low-compliance rate. CONCLUSION: There is marked underuse of guideline-recommended care in this potentially curable cohort. Unexplained provider-level factors significantly contribute to this low-compliance rate. Future studies that identify barriers and modulators of provider-level adoption of guidelines are critical to improving care for patients with bladder cancer.